2014
DOI: 10.1186/1747-597x-9-9
|View full text |Cite
|
Sign up to set email alerts
|

Nonmedical prescription drug users in private vs. public substance abuse treatment: a cross sectional comparison of demographic and HIV risk behavior profiles

Abstract: BackgroundLittle is known regarding the demographic and behavioral characteristics of nonmedical prescription drug users (NMPDUs) entering substance abuse treatment settings, and information on the HIV-related risk profiles of NMPDUs is especially lacking. Participation in substance abuse treatment provides a critical opportunity for HIV prevention and intervention, but successful initiatives will require services appropriately tailored for the needs of NMPDUs.MethodsThis paper compares the HIV risk profiles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Again, these rates appear comparable to, and in the middle range of, those reported in the recent literature for other groups of young PWID which have found syringe-sharing rates ranging from 23%–49% and rates of secondary equipment sharing ranging from 35%–67%. 28,41,44,46 In this literature, as in present sample, rates of secondary equipment sharing typically exceed rates of syringe-sharing, and cookers appear to be the most frequently shared piece of injection paraphernalia. 28,41,44,46 Another concerning finding is participants’ low rate of SEP utilization which appears to differentiate the present sample from many other groups of PWID, such as the street-based, often homeless youth who are the focus of much existing research on young injectors 43,44 .…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Again, these rates appear comparable to, and in the middle range of, those reported in the recent literature for other groups of young PWID which have found syringe-sharing rates ranging from 23%–49% and rates of secondary equipment sharing ranging from 35%–67%. 28,41,44,46 In this literature, as in present sample, rates of secondary equipment sharing typically exceed rates of syringe-sharing, and cookers appear to be the most frequently shared piece of injection paraphernalia. 28,41,44,46 Another concerning finding is participants’ low rate of SEP utilization which appears to differentiate the present sample from many other groups of PWID, such as the street-based, often homeless youth who are the focus of much existing research on young injectors 43,44 .…”
Section: Discussionmentioning
confidence: 51%
“…28,41,44,46 In this literature, as in present sample, rates of secondary equipment sharing typically exceed rates of syringe-sharing, and cookers appear to be the most frequently shared piece of injection paraphernalia. 28,41,44,46 Another concerning finding is participants’ low rate of SEP utilization which appears to differentiate the present sample from many other groups of PWID, such as the street-based, often homeless youth who are the focus of much existing research on young injectors 43,44 . For example, whereas 88% of young San Francisco PWID in the long-running UFO study reported using SEP services in the past month, only 40% of FSU injectors reported using an SEP in the past year, the same proportion as reported obtaining syringes from fellow injectors.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Notably, two new studies conducted with PO misusers in treatment for opioid dependence found that certain subgroups – specifically, polydrug users and younger, White individuals –were more likely to report engaging in sexual risk behavior (Meade et al, 2014; O’Grady, Surratt, Kurtz & Levi-Minzi, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…In the multivariate models, physicians treating greater percentages of such patients reported using fewer risk assessment practices, were less likely to deliver HIV education, and were less likely to recommend HIV testing. Epidemiological studies have shown that many individuals who misuse prescription opioids do inject these substances [ 51 53 ], so perceptions of limited HIV risk among those who use prescription opioids may result in missed opportunities for intervention. Focusing on individuals who inject opioids may be targeting those at highest risk, but individuals who do not inject still face risks if they engage in risky sexual behaviors.…”
Section: Discussionmentioning
confidence: 99%